Pengaruh Kesadaran Wajib Pajak, Pengatahuan Pajak, Sanksi Pajak, dan Tax Amnesty terhadap Kapatuhan Wajib Pajak Kendaraan Bermotor Roda Empat di Kota Kupang dengan Sosialisasi Pajak sebagai Variabel Moderasi (Studi di SAMSAT Kota Kupang) - Ayuni, Ayuni; Manafe, Henny A.; Sonbay, Yolinda Y.; Niha, Simon Sia (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of taxpayer awareness, taxpayer knowledge, tax sanctions and tax amnesty on tax socialization and motor vehicle taxpayer compliance in Kupang City. This research is included in the quantitative research category. The research results show that taxpayer responses to tax amnesty, tax sanctions, taxpayer awareness, and taxpayer compliance with four-wheeled motorized vehicles are positive. Factors that have a major influence on motor vehicle taxpayer compliance are: tax amnesty, tax knowledge, tax sanctions, and taxpayer awareness. The influence of taxpayer awareness, tax knowledge, and tax sanctions on motor vehicle taxpayer compliance can be mitigated by tax socialization. However, the effect of the tax amnesty on motor vehicle taxpayer compliance cannot be mitigated by tax socialization.